2022
DOI: 10.1109/access.2022.3196381
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Weather Forecasting Using Spatial Feature Attention Based LSTM Model

Abstract: Weather prediction and meteorological analysis contribute significantly towards sustainable development to reduce the damage from extreme events which could otherwise set-back the progress in development by years. The change in surface temperature is as one of the important indicators in detecting climate change. In this research, we propose a novel deep learning model named Spatial Feature Attention Long Short Term Memory (SFA-LSTM) model to capture accurate spatial and temporal relations of multiple meteorol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…From Table 7, it can be seen that the BiLSTM [34] tends to have better prediction accuracy than the LSTM [22], which also indicates that the bidirectional network structure can more fully consider the complete information of the sequence data in the forward and backward directions, thus improving the prediction accuracy of the model. At the same time, it can be seen that the improved network based on the attention mechanism [23] has better accuracy, which also indicates that the attention mechanism can assign different attention weights to different stages of temperature change during the training process of the model, so that the model can focus on the key sequence information as much as possible, thus achieving the purpose of enhancing the improvement of temperature prediction accuracy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…From Table 7, it can be seen that the BiLSTM [34] tends to have better prediction accuracy than the LSTM [22], which also indicates that the bidirectional network structure can more fully consider the complete information of the sequence data in the forward and backward directions, thus improving the prediction accuracy of the model. At the same time, it can be seen that the improved network based on the attention mechanism [23] has better accuracy, which also indicates that the attention mechanism can assign different attention weights to different stages of temperature change during the training process of the model, so that the model can focus on the key sequence information as much as possible, thus achieving the purpose of enhancing the improvement of temperature prediction accuracy.…”
Section: Discussionmentioning
confidence: 93%
“…Qiu et al, used LSTM models to predict daily river temperatures and, through experimental analysis of data from the Three Gorges reservoir system, captured the daily average variation of the thermal system more accurately, demonstrating that the LSTM outperformed other methods in predicting the daily average water temperature of rivers [22]. MASOOMA et al used an LSTM model based on a spatial attention mechanism to accurately capture the space and time of multiple meteorological features to predict temperature, and discovered that spatial feature attention captured the interaction of input features on target features, and the study maintained a better prediction accuracy [23]. Song et al, proposed a temporal prediction model, based on LSTM and Kalman filtering, for predicting observations in atmospheric quality datasets, and found that the LSTM-Kalman model had better prediction results when compared with the LSTM model [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most popular methods is using Artificial Neural Networks (ANN) [6]- [8]. The recent success of Deep Learning (DL) methods in other topics, such as image classification [9]- [12], medical signal analysis [13]- [16], and weather forecasting [17], [18] has inspired researchers to apply Deep Learning methods to KWS problems. The examples of the most useful DL methods to perform KWS are Convolutional Neural Networks (CNN) and Recurrent Neural Networks (RNN).…”
Section: A Abstractpotting Methodsmentioning
confidence: 99%
“…RF 2019 (19) Mango: Weather parameters MSE: 0.007 LSTM 2020 (20) Rice: Weather parameters MSE: 0.135 LSTM 2022 (21) Weather Forecasting MSE: 0.08 Hybrid ARIMA-Bi-LSTM2022 (1) Rice:…”
Section: Contributionmentioning
confidence: 99%